1983
DOI: 10.1152/ajpheart.1983.245.6.h1081
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium restriction and development of hypertension in spontaneously hypertensive rats

Abstract: Blood pressure and body weight of conscious spontaneously hypertensive (SHR) and Wistar-Kyoto (WKY) rats were measured up to 16 wk of age in animals started at birth on five different sodium-containing diets. SHR on 9 mumol sodium/g food did not show a rise in basal blood pressure; however, when stressed the SHR still exhibited slightly higher blood pressures than WKY. In SHR on 17 mumol sodium/g food the development of hypertension was blunted compared with that of control (101 mumol/g) diet animals. SHR on 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…However, as with blood pressure, the plasma volume of DS was higher than that of DR fed 1% NaCl; plasma volume was not affected by 5 days of 7% NaCl intake. Other investigators have also reported that net Na + balances do not differ in DR and prehypertensive DS, 28 and Roman and Osborn similar to those of Overbeck et al 5 , who reported that plasma volume, but not extracellular fluid volume, is expanded in hypertensive DS fed a high NaCl diet. Conceivably, an expanded plasma volume in the absence of a net increase of sodium balance may be related to a redistribution of fluid compartments resulting from alterations of vascular or interstitial compliance.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, as with blood pressure, the plasma volume of DS was higher than that of DR fed 1% NaCl; plasma volume was not affected by 5 days of 7% NaCl intake. Other investigators have also reported that net Na + balances do not differ in DR and prehypertensive DS, 28 and Roman and Osborn similar to those of Overbeck et al 5 , who reported that plasma volume, but not extracellular fluid volume, is expanded in hypertensive DS fed a high NaCl diet. Conceivably, an expanded plasma volume in the absence of a net increase of sodium balance may be related to a redistribution of fluid compartments resulting from alterations of vascular or interstitial compliance.…”
Section: Discussionsupporting
confidence: 65%
“…This blood pressure elevation may be attributed to the fact that animals were fed 1% NaCl chow from the time of weaning, and this is a relatively high NaCl intake for the rat. 28 Dahl et al 29 have previously reported that blood pressures are higher in DS fed 1% NaCl than in animals fed 0.4% NaCl. However, we have observed (unpublished observation) that DS and DR fed 0.4% NaCl gain weight at a slower rate than animals fed 1% NaCl.…”
Section: Discussionmentioning
confidence: 96%
“…Using this strain with high blood pressure, numerous studies concerning essential hypertension, including pathophysiology and the effects of food, have been carried out (29,30). Descendants of SHRs, SHRSPs (11) were created through continuous brother-sister mating in a closed colony of SHRs after approximately one decade of mating.…”
Section: Discussionmentioning
confidence: 99%
“…An inbred strain of M-SHRSP shows SBPs of 250 mmHg or higher before 14 weeks of age, and shows more rapid and severe increases in BP and stroke in almost all animals (31). These three types of hypertensive rat substrains, SHR, SHRSP and M-SHRSP, have been used in multiple investigations of pathophysiology, preventive medicine, pharmacology and drug development worldwide (29)(30)(31)(32). Our facility is one of the original places that bred the three types of SHR substrains and families.…”
Section: Discussionmentioning
confidence: 99%
“…These abnormalities presumably result in the animal's exhibiting a variety ofbiochemical and organ defects related to Ca2+ metabolism (5,(7)(8)(9)14). Besides the SHR's having an apparent dependence upon receiving a sufficient dietary Ca2" exposure, reports have suggested a de-pendence of the SHR on an adequate Na' intake (57,58), as sodium restriction in the young SHR was noted to result in growth retardation and premature mortality (57)(58)(59). Dietary potassium does not appear to be a significant factor in the SHRs' blood pressure responses in this study (60).…”
Section: Discussionmentioning
confidence: 99%